The Iceland-Faroe Slope Jet: a conduit for dense water toward the Faroe Bank Channel overflow - Semper, Stefanie; Pickart, Robert S.; Våge, Kjetil; Larsen, Karin Margretha H.; Hátún, Hjálmar; Hansen, Bogi (Nature Communications, 2020)
Dense water from the Nordic Seas passes through the Faroe Bank Channel and supplies the lower limb of the Atlantic Meridional Overturning Circulation, a critical component of the climate system. Yet, the upstream pathways of this water are not fully known. Here we present evidence of a previously unrecognised deep current following the slope from Iceland toward the Faroe Bank Channel using high-resolution, synoptic shipboard observations and long-term measurements north of the Faroe Islands. The bulk of the volume transport of the current, named the Iceland-Faroe Slope Jet (IFSJ), is relatively uniform in hydrographic properties, very similar to the North Icelandic Jet flowing westward along the slope north of Iceland toward Denmark Strait. This suggests a common source for the two major overflows across the Greenland-Scotland Ridge. The IFSJ can account for approximately half of the total overflow transport through the Faroe Bank Channel, thus constituting a significant component of the overturning circulation in the Nordic Seas. publishedVersion